Hippocampal Hyperexcitability is Modulated by Microtubule-Active Agent: Evidence from In Vivo and In Vitro Epilepsy Models in the Rat - Carletti, Fabio; Sardo, Pierangelo; Gambino, Giuditta; Liu, Xin-An; Ferraro, Giuseppe; Rizzo, Valerio (Frontiers in Cellular Neuroscience, 2016)
The involvement of microtubule dynamics on bioelectric activity of neurons and neurotransmission represents a fascinating target of research in the context of neural excitability. It has been reported that alteration of microtubule cytoskeleton can lead to profound modifications of neural functioning, with a putative impact on hyperexcitability phenomena. Altogether, in the present study we pointed at exploring the outcomes of modulating the degree of microtubule polymerization in two electrophysiological epileptiform activity in the rat hippocampus. To this aim, we used in vivo Maximal Dentate Activation (MDA) and in vitro hippocampal epileptiform bursting activity (HEBA) paradigms to assess the effects of nocodazole and paclitaxel, that respectively destabilize and stabilize microtubule structures. In particular, in the MDA paroxysmal discharge is electrically induced, whereas the HEBA is obtained by altering extracellular ionic concentrations. Our results provided evidence that nocodazole 10 µM was able to reduce the severity of MDA seizures, without inducing neurotoxicity as verified by the immunohistochemical assay. In some cases, paroxysmal discharge was completely blocked during the maximal effect of the drug. These data were also in agreement with the outcomes of in vitro HEBA, since nocodazole markedly decreased burst activity that was even silenced occasionally. In contrast, paclitaxel at 10 µM did not exert a clear action in both paradigms. The present study, targeting cellular mechanisms not much considered so far, suggests the possibility that microtubule-active drugs could modulate brain hyperexcitability. This contributes to the hypothesis that cytoskeleton function may affect synaptic processes, relapsing on bioelectric aspects of epileptic activity.